Extracellular vesicle: A magic lamp to treat skin aging, refractory wound, and pigmented dermatosis? - Wu, Haiyan; Zhang, Zhenchun; Zhang, Yuemeng; Zhao, Zhenlin; Zhu, Hongming; Yue, Changwu (Frontiers in Bioengineering and Biotechnology, 2022)
Exposure of the skin to the external stimulus may lead to a serialseries of irreversible dysfunction, such as skin aging, refractory wound, and pigmented dermatosis. Nowadays, many cutaneous treatments have not stroked an expectant balance between cosmetic needs and medical recovery. Extracellular vesicles (EVs), one of the most promising therapeutic tools, are cell-derived nanoparticles carrying various cargoes, such as nucleic acids, lipids and proteins, with the ability to communicate with neighboring or distant cells. A growing amount of Growing number of evidences suggest the significant role of EVs in skin repairs. Herein, we summarized the current findings of EVs therapy in skin aging, refractory wound, and pigmented dermatosis, and also of the novel engineering strategies for optimizing EVs function and therapeutic outcome.